2015
DOI: 10.1093/qje/qjv025
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and Industrialization: Evidence from the Age of Enlightenment *

Abstract: While human capital is a strong predictor of economic development today, its importance for the Industrial Revolution has typically been assessed as minor. To resolve this puzzling contrast, we differentiate average human capital (literacy) from upper-tail knowledge. As a proxy for the historical presence of knowledge elites, we use city-level subscriptions to the famous Encyclopédie in mid-18th century France. We show that subscriber density is a strong predictor of city growth after the onset of French indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(77 citation statements)
references
References 101 publications
4
71
0
2
Order By: Relevance
“…6 In studying the effects of the literary inquisition on the accumulation of human capital, our findings relate to research on the role institutions have in shaping the incentive to acquire human capital. 7 In particular we build on work that has shown that the 'upper tail' knowledge of educated elites played a crucial role in transmitting the Industrial Revolution (Squicciarini and Voigtländer, 2014). 8 Our results are in line with several studies that have established that the effects of shocks can persist for decades or even centuries, notably Becker and Woessmann (2009) who study the impact of the Reformation on the literacy and income of Protestants in nineteenth century Prussia.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…6 In studying the effects of the literary inquisition on the accumulation of human capital, our findings relate to research on the role institutions have in shaping the incentive to acquire human capital. 7 In particular we build on work that has shown that the 'upper tail' knowledge of educated elites played a crucial role in transmitting the Industrial Revolution (Squicciarini and Voigtländer, 2014). 8 Our results are in line with several studies that have established that the effects of shocks can persist for decades or even centuries, notably Becker and Woessmann (2009) who study the impact of the Reformation on the literacy and income of Protestants in nineteenth century Prussia.…”
Section: Introductionsupporting
confidence: 71%
“…Human capital and especially upper tail human capital is a crucial ingredient for both innovation and convergence (Squicciarini and Voigtländer, 2014). In Qing China the persecution of intellectuals caused fewer individuals to acquire upper tail human capital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No study has been able to show that the positive association between education levels and per capita income in most European economies between 1550 and 1900 reflects a causal effect of education on growth rather than rising incomes enabling people to consume more education. This lack of evidence has led recent literature to focus on the contribution of the knowledge and skills of particular groups (Kelly et al 2014, Squicciarini and Voigtländer 2015, Dittmar and Meisenzahl 2016. One study does claim to provide evidence that education of the general population had an important causal influence on industrialisation in the nineteenth century.…”
Section: Introductionmentioning
confidence: 99%